HARMONY AMONG RELIGIUS COMMUNITIES IN BAGOREJO VILLAGE SRONO DISTRICT: Kerukunan Antar Umat Beragama Di Desa Bagorejo Kecamatan Srono - Ahmad Mughni Labib; I Kadek Yudiana; Sahru Romadloni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Religious diversity phenomenon in Bagorejo Village is one of the multicultural social conditions among societies in daily life whice cannot be separated. The country’s constitution provides freedom to choose religion and carry out worship according to the their religious beliefs. The aim of this study is to determine the interfaith harmony background, examine the implementation of interfaith harmony background, examine the implementation of interfaith harmony, as well explore the character values of interfaith harmony in Bagorejo village, Srono District. This study uses qualitative approach with a descriptive research thpe. The data collection techniques are interviews, observation, and documentation. The data validity test technique used is data triangulation, namely researcher triangulation, theory triangulation, and method triangulation. The study result shows that Bagorejo Village still maintains interfaith harmony. Is is based on tolerance, mutual cooperation, and upholds the importance of brotherhood among communities. A sense of tolerance can be seen in the daily life among societies in Bagorejo village during religious and social events. It creates character values such as tolerance, mutual cooperation, and brotherhood in society, which are reflected in interfaith harmony in Bagorejo Village.